Comprehensive Approach to Differential Diagnosis of Large Salivary Gland Neoplasms - Maksudov, Dilshod Davronovich (American Journal of Bioscience and Clinical Integrity, 2025)
This article explores a comprehensive diagnostic framework for differentiating large salivary gland neoplasms using clinical, imaging, and histopathological parameters. The study emphasizes the role of advanced imaging modalities, particularly ultrasonography, MRI, and fine-needle aspiration cytology (FNAC), in improving diagnostic precision. Based on 70 patients examined between 2020 and 2024, the research demonstrates that a multimodal diagnostic strategy combining morphological and functional data provides the highest sensitivity and specificity for tumor characterization. The proposed approach enhances the accuracy of distinguishing benign from malignant neoplasms, thus facilitating optimal treatment planning and improving patient outcomes.